Microstructure and mechanical properties of 7075 aluminum alloy welds by gas tungsten arc welding with trailing ultrasonic rotating extrusion - Rongtao Zhu; Xinghong Ji; Bo Yuan; Zhaofeng Liang; Peng Du; Liang Zhang; Zhiwen Xie (Journal of Materials Research and Technology)
In this investigation, gas tungsten arc welding (GTAW) and gas tungsten arc welding with trailing ultrasonic rotating extrusion (U-RE-GTAW) were applied to 7075 aluminum alloys. Qualitative comparisons and analyses were carried out to investigate the effects of the ultrasonic rotary extrusion-assisted technology on GTAW processes. The weld joints fabricated by GTAW and U-RE-GTAW were examined using X-ray diffraction (XRD), scanning electron microscopy (SEM), electron backscatter diffraction (EBSD), and transmission electron microscopy (TEM) techniques. Concurrently, the tensile strength and fatigue characteristics were assessed at ambient temperature. The experimental outcomes indicated that the U-RE-GTAW process mitigated porosity within the weld region and substantially augmented dislocation density, while concurrently achieving a notable reduction in grain size and an increase in the volume fraction of secondary phases due to the synergistic effects of ultrasonic oscillation and rotational extrusion. The enhancement in tensile and fatigue resistance of the welded joint was attributed to the strengthening mechanisms associated with these microstructural alterations. Specifically, the ultimate tensile strength exhibited a 20.4% increase, and the elongation at break was elevated by 46.3%. At stress amplitudes of 190 MPa, 160 MPa, and 100 MPa, the fatigue strength of the welded joints was enhanced by 67%, 55%, and 32%, respectively. A quantitative analysis was conducted to elucidate the impact of diverse strengthening mechanisms on the welded joints. It was concluded that dislocation strengthening is the predominant factor contributing to the superior performance of the U-RE-GTAW specimens.